The efficient generation of 4D BIM construction schedules: A case study of the Nanterre 2 CESI project in France - Doukari, Omar; Seck, Boubacar; Greenwood, David (Frontiers in Built Environment, 2022)
Building Information Modelling (BIM) is now globally recognised, though its adoption remains inconsistent and variable between and within the construction sectors of different countries. Originating as an enhanced 3D design tool, BIM has been extended into a wide range of functional applications. One such application is ‘4D BIM’ which involves linking the tasks in a project’s construction schedule to its object-orientated 3D-model to improve the delivery of projects and enable animations of the process to be visualized. To achieve this, the 3D objects within the aggregated design model must be linked with each activity in the construction schedule. Ideally this can be automatically generated, but in reality, because the 3D and 4D models are created separately and at different stages of the project, this is not currently possible, and the process requires considerable manual effort. Furthermore, the levels of maturity and expertise in using BIM amongst the project participants still varies considerably. This generates collaboration problems within the project and adds further obstacles to the ability to derive full benefits from BIM. The authors propose an approach that minimises this effort and illustrate its use through a case study in the form of the Nanterre 2 CESI building in France. The CESI four-phase process aims to help project participants to fully exploit the potential of 4D BIM and enables: (i) a clear expression of the 4D BIM objectives; (ii) the identification of information requirements and relevant workflows to achieve these objectives; (iii) the implementation of a project schedule; and (iv) BIM model production to suit the 4D BIM use case.